Resource Mobilization Policy Guidelines - Kabale University (Kabale University, 2022)
These guidelines have been designed to provide structures and responsibilities, procedure and systems that support the implementation of the Kabale University Resource Mobilization Policy, 2021. It is intended to enhance capacity of University stakeholders in securing resources for Kabale University’s mandate as documented in the Statutory Instrument No. 36 of July 2015, establishment of Kabale University